2016
DOI: 10.1002/aenm.201502458
|View full text |Cite
|
Sign up to set email alerts
|

Bandgap‐Tunable Cesium Lead Halide Perovskites with High Thermal Stability for Efficient Solar Cells

Abstract: Highest reported efficiency cesium lead halide perovskite solar cells are realized by tuning the bandgap and stabilizing the black perovskite phase at lower temperatures. CsPbI2Br is employed in a planar architecture device resulting in 9.8% power conversion efficiency and over 5% stabilized power output. Offering substantially enhanced thermal stability over their organic based counterparts, these results show that all‐inorganic perovskites can represent a promising next step for photovoltaic materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

53
1,228
2
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 1,389 publications
(1,290 citation statements)
references
References 36 publications
53
1,228
2
7
Order By: Relevance
“…Solar cells comprising all-inorganic perovskite NCs (CsPbI 3 ) have reached efficiencies of 9.8%, still significantly lower than solar cells made of hybrid perovskite NCs. 118 Most of the semiconductor materials displaying high photoconversion efficiencies can act as efficient photodetectors. In light of this, perovskite NCs have also been employed as broadband photodetectors, even though this research field is rather new.…”
Section: Perovskite Ncs In Solar Cells and Photodiodesmentioning
confidence: 99%
“…Solar cells comprising all-inorganic perovskite NCs (CsPbI 3 ) have reached efficiencies of 9.8%, still significantly lower than solar cells made of hybrid perovskite NCs. 118 Most of the semiconductor materials displaying high photoconversion efficiencies can act as efficient photodetectors. In light of this, perovskite NCs have also been employed as broadband photodetectors, even though this research field is rather new.…”
Section: Perovskite Ncs In Solar Cells and Photodiodesmentioning
confidence: 99%
“…120,121 However recently, cation mixtures have gained attention as a means to increase the absorber material's resistance to moisture and heat degradation. These stability gains were achieved by substituting MA with formamidinium (FA), 122 cesium (Cs) cations, [123][124][125][126] or a mixture of the two (Figure 3(b) and 3(d)). 5,127-131 Eperon et al reported that degradation was considerably slowed for FAPbI 3 compared to MAPbI 3 when heated at 150…”
mentioning
confidence: 99%
“…Fully inorganic cesium-based perovskite has gained interest due to their potential of withstanding high temperatures. [123][124][125][126] CsPbI 3 forms in a cubic (pm3m) perovskite structure with a band gap of 1.73 eV. 122,123 Unfortunately, CsPbI 3 is highly unstable in this crystal structure when exposed to air and quickly undergoes a reversible phase transition to a yellow orthorhombic phase material, unsuitable for solar cell applications.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[108,109] However, the lead halide perovskite materials can be easily dissolved and degraded when exposed to ambient humidity, thus showing low stability against humid environment for long-term operation. [110,111] To address this issue, Zhao et al reported the first self-healing perovskite solar cell based on an insulating polymer scaffold structure.…”
Section: Photovoltaicsmentioning
confidence: 99%